Partial endonuclease digestion mapping of restriction sites using PCR-amplified DNA. - Morales, J C; Patton, J C; Bickham, J W (Genome Research, 1993)
Although direct DNA sequencing is now readily available, restriction enzyme analyses are still widely used in population genetics and molecular systematics studies. These analyses provide cheaper and faster ways to assay patterns of nucleotide differentiation across a large number of individuals. In this paper, we introduce a new approach to restriction enzyme analyses in which high-resolution restriction site maps are obtained from partial digestions of PCR products. This procedure increases the level of resolution at least an order of magnitude over the double-digestion method for restriction enzyme mapping, can target specific DNA regions with the use of specific primers, and, because it uses chemiluminescent detection of DNA, can be easily implemented in laboratories that lack the necessary setups to handle radioactive substances.
10.1101/gr.2.3.228